Limited spatial rescue potential for coral reefs lost to future climate warming. Issue 11 (22nd July 2022) - Greiner, Ariel; Andrello, Marco; Darling, Emily; Krkošek, Martin; Fortin, Marie‐Josée
Abstract: Aim: The aim was to determine reef connectivity and future coral cover levels under global scenarios of coral bleaching loss and potential recovery. Location: Global coral reefs. Time period: Present‐day to 2100. Major taxa studied: Scleractinian coral. Methods: We used a global coral larval dispersal model that describes population connectivity among reefs at a resolution of ⅙° × ⅙° ( c . 18 km × 18 km) cells. To simulate different patterns of bleaching events, we ran three scenarios at different levels of coral reef habitat loss followed by a reseeding of coral larvae from surviving reefs to simulate recovery. Results: We found a total of 604 distinct reef networks, but more than half of the world's reef cells are contained in six large coral reef networks (294–5, 494 cells), whereas the rest form smaller networks. In the bleaching scenario where previously identified predicted climate refugia were maintained, initial connectivity was largely preserved even when 71% of global coral reef habitat was lost, but the relict reef cells were unable to reseed even 50% of former coral reef habitat because many of the relict reefs are in the same networks as each other. In scenarios where refugia were lost first or with random loss, less of the initial connectivity was maintained, but more widespread reseeding was possible because more reef cells within smaller networks were maintained. Main conclusions: Our findings highlight the importance of maintaining functional coral reef habitat outside of predicted climate refugia to sustain connectivity globally, and suggest an important role for "stepping stone" reefs between the climate refugia. Without attention to these issues of habitat loss and connectivity, much of global coral reef habitat might not be reseeded without human intervention.